2020
DOI: 10.1002/jcla.23216
|View full text |Cite
|
Sign up to set email alerts
|

Identification of and solution for false D‐dimer results

Abstract: D-dimer is a specific degradation product derived from fibrinolytic cross-linked fibrin clots and mainly reflects fibrinolysis. 1 The production of D-dimer requires the sequential activity of three enzymes: thrombin, factor XIIIa, and plasmin. 2 When blood coagulation occurs, thrombin acts on fibrinogen and transforms into cross-linked fibrin under the action of factor XIIIa. At the same

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Published reports on antibody interference in D-dimer assays are rare. Cases described in the literature showed that interference in D-dimer assays occurs in both men and women of different ages (3-86 years) and with or without underlying diseases that could impact autoantibody status [ [5] , [6] , [7] , [8] ]. Interestingly, all described cases showed interference on latex-enhanced immunoturbidimetric D-dimer assays and occurred with monoclonal antibodies of different manufacturers, different antibody epitopes, and in reagents with different blocking agents [ 7 ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Published reports on antibody interference in D-dimer assays are rare. Cases described in the literature showed that interference in D-dimer assays occurs in both men and women of different ages (3-86 years) and with or without underlying diseases that could impact autoantibody status [ [5] , [6] , [7] , [8] ]. Interestingly, all described cases showed interference on latex-enhanced immunoturbidimetric D-dimer assays and occurred with monoclonal antibodies of different manufacturers, different antibody epitopes, and in reagents with different blocking agents [ 7 ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In contrast, D-dimers are produced during plasmin breakdown of cross-linked fibrin generated through activation of coagulation. 27 Thus, a high FDP:D-dimer ratio suggests hyperfibrinolysis. Although some studies have proposed that immediate overactivation of the protein C pathway may also contribute to hyperfibrinolysis in the setting of traumatic shock, evidence for this mechanism is mixed.…”
Section: Fibrinolysis In Traumatic Brain Injurymentioning
confidence: 99%
“…This not specific cross-linking may result in generation of a falsely positive results. The more common cause of such interference was the presence of heterophilic (or human anti mouse) antibodies [8][9][10].…”
Section: Introductionmentioning
confidence: 99%